Evaluation of the Psychometric Properties of the Movement Assessment Battery Second Edition (M-ABC2): A Cross-Sectional Study - Eleonora Scarfò; Michela Ranucci; Anna Berardi; Rachele Simeon; Giovanni Galeoto (MDPI AG, 2024)
This cross-sectional study assessed the psychometric properties of the movement assessment battery for children second edition (M-ABC2) in Italian children with typical development, focusing on reliability and percentile rank establishment. The M-ABC2 is widely utilized but lacks validation in Italian populations. One hundred and eight children were recruited. Test-retest reliability was evaluated using intra-class correlation coefficients (ICCs), indicating good to excellent reliability across age groups, albeit with outliers requiring further scrutiny. Standard scores and percentile ranks were established, revealing age-related variations in motor performance. Noteworthy differences in completion times and error rates were observed among the age groups, highlighting the dynamic nature of motor development. While the findings provide valuable insights for clinicians and researchers, limitations such as sample size and geographic representation should be addressed in future studies. This study underscores the importance of employing reliable assessment tools for comprehensive understanding and effective intervention in pediatric motor development.